KAJIAN PENAMBAHAN TEPUNG TEMPE PADA PEMBUATAN KUE BASAH TERHADAP DAYA TERIMA KONSUMEN - Murni, Mustika (UPN VETERAN JAWA TIMUR, 2010)
The aim of this research to know influence of addition of tempeh flour in making cakes to consumer acceptance. The treatments using tempeh flour is 0% (as control),5%, 10%, 15%, 20% and 25% will be tested organoleptic test to taste, color, texture and flavor. These data will be analized with Friedman test. The result of research showed that for nagasari and kelepon the treatment of addition tempeh flour 10% and lumpia 25% with hedonic score for nagasari: taste 3.90 (like), color 3.90 (like), texture 3.95 (like), flavor 3.90 (like); for to kelepon: taste 4,00 (like), color 3.95 (like), texture 4.00 (like), flavor 4.00 (like) and lumpia: taste 4.75 (very like), color 3.90 (like), texture 3.95 (like), flavor 3.60 (like).Keywords : tempeh flour, cakes, organoleptic test.